IMPLEMENTASI STATIC NAT TERHADAP JARINGAN VLAN MENGGUNAKAN IP DYNAMIC HOST CONFIGURATION PROTOCOL (DHCP) - Juwanda Natali; Fajrillah Fajrillah; T.M. Diansyah (Department of Science and Technology Ibrahimy University, 2016)
To build a network interconnect Local Area Network (LAN) that will be needed in the form of Virtual groups Local Area Network (LAN). DHCP IP address given by the router to the PC located in the network. NAT (Network Address Translation) is one method that is used as an IP translation to gain entrance into a different network. NAT (Network Address Translation) can allow a host to go into different networks without allowing the host intended to tap into their networks using VLAN With the two different networks into a single switch can be connected. Giving DHCP IP will allow the network administrator to provide the IP address to a PC for IP assigned automatically by the router. An IP host is forwarded in a network with NAT.